Web Mining Opportunities and Privacy Challenges: Exploring techniques, challenges, and methods in web mining (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper is a work on survey on the existing techniques of web mining and the issues related to it. The World Wide Web acts as an interactive and popular way to transfer information. Due to the enormous and diverse information on the web, the users cannot make use of the information very effectively and easily. Data mining concentrates on non-trivial extraction of implicit previously unknown and potential useful information from the very large amount of data. Web mining is an application of data mining which has become an important area of research due to vast amount of World Wide Web services in recent years. The aim of this paper is to provide the past and current techniques in Web Mining. The research work done by different users depicting the pros and cons are discussed. It also gives the overview of development in research of web mining and some important research issues related to it.The web mining introduces unique computational and statistical challenges, including scalability and storage bottleneck, noise accumulation, spurious correlation and measurement errors. These challenges are distinguished and require new computational and statistical paradigm. This paper presents the literature review about the web Mining and the Opportunities and Privacy challenges with emphasis on the distinguished features of web mining. It also discusses some methods to deal with web mining.